The Effect Of Leadership Style And Work Environment On Employee Performance PT. Green Asia Food Indonesia Tasikmalaya City - Kamil, Muahammad Rifqi; barlian, Barin; Sutrisna, Arga (Universitas Dehasen Bengkulu, 2024)
This study aims to determine the effect simultaneously and partially between Leadership Style and Work Environment on Employee Performance at PT. Green Asia Food Indonesia Tasikmalaya City. The research method used is a survey method with a quantitative approach. The sampling technique used the saturated sample method with a total sample of 52 people. Data collection techniques using online and offline questionnaires. The data used is primary data. The analytical tool used in this study is multiple regression using SPSS 26. The results show that leadership style and work environment simultaneously have a significant effect on employee performance. Partially, leadership style has a significant effect on employee performance. Partially, the work environment has a significant effect on employee performance.